An Autophagy‐Disrupting Small Molecule Promotes Cancer Cell Death via Caspase Activation. (24th July 2021) - Park, Sang‐Hyun; Shin, Insu; Kim, Gun‐Hee; Ko, Sung‐Kyun; Shin, Injae
Abstract: A novel autophagy inhibitor, autophazole (Atz), which promoted cancer cell death via caspase activation, is described. This compound was identified from cell‐based high‐content screening of an imidazole library. The results showed that Atz was internalized into lysosomes of cells where it induced lysosomal membrane permeabilization (LMP). This process generated nonfunctional autolysosomes, thereby inhibiting autophagy. In addition, Atz was found to promote LMP‐mediated apoptosis. Specifically, LMP induced by Atz caused release of cathepsins from lysosomes into the cytosol. Cathepsins in the cytosol cleaved Bid to generate tBid, which subsequently activated Bax to induce mitochondrial outer membrane permeabilization (MOMP). This event led to cancer cell death via caspase activation. Overall, the findings suggest that Atz will serve as a new chemical probe in efforts aimed at gaining a better understanding of the autophagic process. Abstract : A novel autophagy inhibitor (autophazole, Atz) is reported which was identified by cell‐based high‐content screening of an imidazole library. Autophazole was found to disrupt lysosomal function, thereby leading to inhibition of autophagy. In addition, Atz induces lysosomal membrane permeabilization‐associated apoptotic cancer cell death.